2003
DOI: 10.1186/1471-2350-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CHEK2*1100delC in New York breast cancer cases and controls

Abstract: Background: The 1100delC CHEK2 allele has been associated with a 1.4-4.7 fold increased risk for breast cancer in women carrying this mutation. While the frequency of 1100delC was 1.1-1.4% in healthy Finnish controls, the frequency of this allele in a North American control population and in North American breast cancer kindreds remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
4
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 7 publications
8
68
4
1
Order By: Relevance
“…11 The prevalence of the 1100delC variant varies among populations. The frequency in other Northern European populations is approximately 1%, 11 comparable to the frequency in Finland but a lower frequency has been reported in a New York study, 24 and the variant was not found among 400 familial breast cancer patients or 400 healthy controls in a Spanish study. 25 The markedly elevated frequency of 1100delC in breast cancer cases with a strong family history suggests this mutation acts as a low-penetrance breast cancer susceptibility allele whose risk may be modified by other low penetrance breast cancer susceptibility alleles, as suggested by recent genetic epidemiological models.…”
Section: Frequency Of the I157t Variant In Breast Cancer Patientsmentioning
confidence: 78%
“…11 The prevalence of the 1100delC variant varies among populations. The frequency in other Northern European populations is approximately 1%, 11 comparable to the frequency in Finland but a lower frequency has been reported in a New York study, 24 and the variant was not found among 400 familial breast cancer patients or 400 healthy controls in a Spanish study. 25 The markedly elevated frequency of 1100delC in breast cancer cases with a strong family history suggests this mutation acts as a low-penetrance breast cancer susceptibility allele whose risk may be modified by other low penetrance breast cancer susceptibility alleles, as suggested by recent genetic epidemiological models.…”
Section: Frequency Of the I157t Variant In Breast Cancer Patientsmentioning
confidence: 78%
“…Highest population frequencies have been found in the Netherlands (1.3-1.6%) and in Finland Kleibl et al, 2005), Italy (0.11%, Caligo et al, 2004), USA (0.3-0.4%, Offit et al, 2003;Friedrichsen et al, 2004) and Canada (0.2%, Bernstein et al, 2006); the variant has not been detected in the Spanish population (Osorio et al, 2004).…”
Section: Chek2 In Li-fraumeni Syndromementioning
confidence: 99%
“…After the BRCA1 and BRCA2 proteins were cloned and their association with family breast cancer was detected (Miki Y et al, 1994;Wooster R et al, 1995), greater emphasis was placed on the candidate gene of breast cancer. The cell cycle-checkpoint kinase 2 gene, or CHEK2, was widely researched as a strong candidate gene for breast cancer susceptibility (Vahteristo et al, 2002;Sodha et al, 2002;Offit et al, 2003;CHEK2 Breast Cancer Consortium, 2004;Dufault et al, 2004;Friedrichsen et al, 2004;Mateus Pereira et al, 2004;Baeyens et al, 2005;Kleibl et al, 2005;Rashid et al, 2005;Bernstein et al, 2006;Einarsdóttir et al, 2006;Cybulski et al, 2007;Weischer et al, 2007;Zhang et al, 2008;Fletcher et al, 2009;McInerney et al, 2010;Iniesta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%